New approach in the procedures of gas freeing and inspecting confined and enclosed spaces in maritime vessels - Stavrakakis, P.; Chalaris, Michail; Dourmas, Georgios N.; Sarafis, Pavlos (My University, 2010)
In naval vessels, air quality monitoring in general and specifically gas free-testing is an important and demanding task. Gas-free procedures include measurements of oxygen levels, explosive (% LEL) and toxic gases by qualified and experienced personnel through various handheld devices. However, confined spaces of warships (fuel tanks, CHT spaces, voids, etc.) along with other special features appeared in ships (low accessibility, poor lighting, moisture, lack of air movements, etc.) provide with more difficulties regarding air quality monitoring. A versatile handheld field device, originally developed for early location of entrapped people, specially modified and designed is tested for supporting the air quality monitoring procedure of naval spaces. The device developed enables chemical, visual and audio capabilities. Special performance characteristics such as robustness, corrosive resistant, easy decontamination, explosive proof and minimum electromagnetic signature are investigated for optimum performance. This all-in-one device will possibly provide on-line and on-site measurements offering to fleet crewmembers and shipyards personnel an easy-to-use reliable tool for performing air quality monitoring effectively, efficiently and quickly. Furthermore, the cost for maintenance and inspection of confined spaces will be probably reduced without risking personnel safety, while adding to air quality monitoring the abilities of audio and visual abilities for surveillance.
Keywords: Air quality monitoring; Confined spaces; Gas-free; Gas-free testing